Methanogen Diversity in Indigenous and Introduced Ruminant Species on the Tibetan Plateau. (28th April 2016) - Huang, Xiao Dan; Martinez-Fernandez, Gonzalo; Padmanabha, Jagadish; Long, Ruijun; Denman, Stuart E.; McSweeney, Christopher S.
Abstract : Host factors are regarded as important in shaping the archaeal community in the rumen but few controlled studies have been performed to demonstrate this across host species under the same environmental conditions. A study was designed to investigate the structure of the methanogen community in the rumen of two indigenous (yak and Tibetan sheep) and two introduced domestic ruminant (cattle and crossbred sheep) species raised and fed under similar conditions on the high altitude Tibetan Plateau. The methylotrophic Methanomassiliicoccaceae was the predominant archaeal group in all animals even though Methanobrevibacter are usually present in greater abundance in ruminants globally. Furthermore, within the Methanomassiliicoccaceae family members from Mmc. group 10 and Mmc. group 4 were dominant in Tibetan Plateau ruminants compared to Mmc. group 12 found to be highest in other ruminants studied. Small ruminants presented the highest number of sequences that belonged to Methanomassiliicoccaceae compared to the larger ruminants. Although the methanogen community structure was different among the ruminant species, there were striking similarities between the animals in this environment. This indicates that factors such as the extreme environmental conditions and diet on the Tibetan Plateau might have a greater impact on rumen methanogen community compared to host differences.